A model of cognitive loads in massively multiplayer online role playing games - Ang, Chee Siang; Zaphiris, Panayiotis; Mahmood, Shumaila (My University, 2007)
Being one of the most commercially successful entertainment software applications, massively multiplayer online role playing games (MMORPGs) continue to expand in term of the revenue they generate as well as the involvement of users who congregate in their virtual space and form communities around them to support each other. Unlike conventional offline computer games, or networked games with limited numbers of players, MMORPGs are not merely software applications as they are usually seen as a space with complicated dynamics of social interactions. Hence, it is believed that playing these games might cause cognitive overload problems among the players as they have to constantly interact with the game world as well as with other users. We conducted an exploratory study using qualitative methods to explore cognitive overloads in Maple Story, a typical MMORPG. Our results reveal that several types of cognitive overloads emerge during the game playing. While some of these overloads pose serious problems even to expert players, players seem to develop strategies to overcome them. It is found that some forms of cognitive load are actually desirable in order to make the game challenging. We have also created a set of recommendations that can help game developers handle cognitive load problems in MMORPGs.
Keywords: Games; MMORPG; Cognitive load